2023
DOI: 10.3389/fpubh.2022.1016819
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the association between circulating trace elements, metabolic risk factors, and the adherence to a Mediterranean diet among children and adolescents with obesity

Abstract: Diet is one of the most important modifiable lifestyle factors for preventing and treating obesity. In this respect, the Mediterranean diet (MD) has proven to be a rich source of a myriad of micronutrients with positive repercussions on human health. Herein, we studied an observational cohort of children and adolescents with obesity (N = 26) to explore the association between circulating blood trace elements and the degree of MD adherence, as assessed through the KIDMED questionnaire. Participants with higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…Herein, the evaluation of the food intake questionnaires showed that the frequency of consumption of seafood products (i.e., the main source of arsenic) was significantly lower in participants with delayed insulin response and was in turn positively correlated with blood arsenic levels. This concurs with recent data evidencing a direct association between the adherence to a Mediterranean diet and plasma arsenic levels among children with obesity [ 39 ]. Thus, these results support the rationale that nutritional deficiencies could be, at least in part, responsible for the inverse association between arsenic and IR severity among children and adolescents with obesity.…”
Section: Discussionsupporting
confidence: 93%
“…Herein, the evaluation of the food intake questionnaires showed that the frequency of consumption of seafood products (i.e., the main source of arsenic) was significantly lower in participants with delayed insulin response and was in turn positively correlated with blood arsenic levels. This concurs with recent data evidencing a direct association between the adherence to a Mediterranean diet and plasma arsenic levels among children with obesity [ 39 ]. Thus, these results support the rationale that nutritional deficiencies could be, at least in part, responsible for the inverse association between arsenic and IR severity among children and adolescents with obesity.…”
Section: Discussionsupporting
confidence: 93%
“…These results were consistent with other studies that evaluated the anti-obesity effect of diets. [54][55][56][57]…”
Section: Effect Of Sourdough Bread Intervention On the Histopathologi...mentioning
confidence: 99%
“…In this venue, trace elements are considered pivotal components of redox metabolism, the immune system, and hormone function. [11][12][13] A few authors have previously investigated the association between childhood obesity, metabolic risk factors, and circulating metal concentrations, [14][15][16][17][18] but the impact of puberty on these perturbations remains unexplored. In this work, we studied the influence of hormonal changes during puberty in modulating the oxidative and inflammatory milieu in childhood obesity, with a particular focus on metal metabolism regulation.…”
Section: Introductionmentioning
confidence: 99%